2018
DOI: 10.1186/s12887-018-1179-7
|View full text |Cite
|
Sign up to set email alerts
|

Testing the feasibility of eliciting preferences for health states from adolescents using direct methods

Abstract: BackgroundMeasuring adolescents’ preferences for health states can play an important role in evaluating the delivery of pediatric healthcare. However, formal evaluation of the common direct preference elicitation methods for health states has not been done with adolescents. Therefore, the purpose of this study is to test how these methods perform in terms of their feasibility, reliability, and validity for measuring health state preferences in adolescents.MethodsThis study used a web-based survey of adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Other studies show varying amounts of test-retest reliability in (c)TTO studies. 1,19,20 Our study showed a test-retest reliability in cTTO data comparable with that of Purba et al 20 (95%), although different definitions of test-retest reliability were used.…”
Section: Preference-based Assessmentssupporting
confidence: 85%
“…Other studies show varying amounts of test-retest reliability in (c)TTO studies. 1,19,20 Our study showed a test-retest reliability in cTTO data comparable with that of Purba et al 20 (95%), although different definitions of test-retest reliability were used.…”
Section: Preference-based Assessmentssupporting
confidence: 85%
“…There are concerns around whether it is acceptable and appropriate to administer preference elicitation tasks due to the possibility that consideration of dead or trading between quality of life and quantity of life may cause upset or distress for adolescents [41]. The existence of TTO studies that have been undertaken with adolescents using preference elicitation tasks for both their own health and/or for hypothetical health states that involve consideration of being dead (potentially framed as trading of years left to live) [42][43][44][45][46] suggests that these tasks may be acceptable and appropriate. However, the authors are not aware of any studies designed to explicitly test this.…”
Section: Ethical Concerns Around Preference Elicitation With Adolescentsmentioning
confidence: 99%
“…The plausibility of a life expectancy of 10 years from today for adolescents and younger adults is questionable (and may be implausible for many adults), and potentially this could impact on preferences (though the authors are not aware of any studies examining this). For this reason some studies have used different time frames, for example 60 years [43]. However, increasing the time frame beyond 10 years would be implausible for the elderly participants in the sample.…”
Section: Preference Elicitation Techniquementioning
confidence: 99%
“…Several groups are deriving utility weights for health states described by the generic non-preference-weighted PedsQL via mapping to the CHU-9D and EQ-5D [ 43 48 ]. Another promising area of research is using direct elicitation methods including discrete choice experiments to value improvements in children’s health [ 32 , 49 51 ].…”
mentioning
confidence: 99%